2011
DOI: 10.1111/j.1349-7006.2011.02050.x
|View full text |Cite
|
Sign up to set email alerts
|

Combination treatment with fulvestrant and various cytotoxic agents (doxorubicin, paclitaxel, docetaxel, vinorelbine, and 5‐fluorouracil) has a synergistic effect in estrogen receptor‐positive breast cancer

Abstract: Patients with estrogen receptor (ER)-positive breast cancers have a better prognosis than those with ER-negative breast cancers, but often have low sensitivity to chemotherapy and a limited survival benefit. We have previously shown a combination effect of taxanes and fulvestrant and suggested that this treatment may be useful for ER-positive breast cancer. In this study, we evaluated the effects of combinations of hormone drugs and chemotherapeutic agents. In vitro, the effects of combinations of five chemoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 24 publications
2
38
0
Order By: Relevance
“…Our results provide the first evidence that dovitinib treatment sensitizes FGFR2 mutant cells to pure steroidal selective ER modulators such as ICI182.780. In breast cancer, some authors have reported in vitro and in vivo assays using combinational therapy using ICI182.780 with chemotherapeutic agents such as Doxorubicin (46); Paclitaxel (47), Vinorelbine (48), and Doxotaxel (49), although the results are quite promising, the number of studies is limited and combinational treatment using modern hormone therapy with chemotherapeutic agents has not been examined toughly; specially in endometrial carcinoma treatment. However, several experimental approaches using anticancer kinase inhibitors in tumor cells have revealed numerous feedback loops and have shown that blocking one signaling pathway can block tumor growth partially, but they are not sufficient to cause a complete tumor regression, thereby allowing resistant cells to emerge (50).…”
Section: Discussionmentioning
confidence: 99%
“…Our results provide the first evidence that dovitinib treatment sensitizes FGFR2 mutant cells to pure steroidal selective ER modulators such as ICI182.780. In breast cancer, some authors have reported in vitro and in vivo assays using combinational therapy using ICI182.780 with chemotherapeutic agents such as Doxorubicin (46); Paclitaxel (47), Vinorelbine (48), and Doxotaxel (49), although the results are quite promising, the number of studies is limited and combinational treatment using modern hormone therapy with chemotherapeutic agents has not been examined toughly; specially in endometrial carcinoma treatment. However, several experimental approaches using anticancer kinase inhibitors in tumor cells have revealed numerous feedback loops and have shown that blocking one signaling pathway can block tumor growth partially, but they are not sufficient to cause a complete tumor regression, thereby allowing resistant cells to emerge (50).…”
Section: Discussionmentioning
confidence: 99%
“…MCF-7 cells (1.1x10 4 ) were seeded in a 6-well plate. After cell adherence and rapid growth, cells were treated with TPI at different concentrations for 24 h, after which cold PBS was used to stop each treatment.…”
Section: Methodsmentioning
confidence: 99%
“…Currently, breast cancer is classified into five major groups on the basis of molecular profiling. Doxorubicin, gemcitabine, and taxanes are major clinical chemotherapeutic agents (4,5) Side-effects and drug resistance are common problems in patients taking long-term medication (6).…”
Section: Introductionmentioning
confidence: 99%
“…It is useful especially in patients with advancer BC and as second-line therapy in TAM-resistant tumors [36] . Fulvestrant sensitizes ER-negative BC to chemotherapy, showing a synergistic action with various cytotoxic agents, such as docetaxel [39,40] . In the treatment of patients with metastatic ER+ BC, the combination of fulvestrant plus an AI (anastrozole) was superior to anastrozole alone, and fulvestrant as single-drug therapy represents a reasonable alternative to AIs [41,42] .…”
Section: Down-regulatorsmentioning
confidence: 99%